EKSISTENSI KOMNAS HAM DITINJAU DARI HUKUM KETATANEGARAAN REPUBLIK INDONESIA - Galang Asmara (Perspektif, 2002)
Violation of human rights and law that happened in the past era has been a main reason of National Commission of Human Rights (Komnas HAM) formation. Its aim is to protect and make sure the implementation of human rights in Indonesia is worked out as expected. In constitutions of Human Rights, i.e. UU No. 39/1999, National Commission of Human Rights is a institution positioned as the same level with other national institutions. This position, however, will raise a legal problem as it is not in accordance with power sharing system stated in UUD 1945.